Pengelolaan Bantuan Langsung Tunai Dana Desa Kecamatan Tebo Tengah Kabupaten Tebo - Yopi Ispa, Ari; Prihatiningsih, Astuti; Marlina , Teti (ILTIZAM Journal of Shariah Economics Research, 2025)
The COVID-19 pandemic has spread throughout the world and significantly impacted the people’s economy. The government initiated a village fund direct cash assistance (BLT-DD) program to help poor rural communities affected by COVID-19. Transparency in The planning, distribution, and reporting of this program is urgently needed. In addition, accountability must be carried out clearly so that there is no misappropriation or embezzlement of funds. This study aims to analyze the effect of transparency and accountability on the management of Village Fund Direct Cash Assistance. This study uses primary data obtained from the direct distribution of questionnaires. The method used in this study is quantitative and uses multiple linear regression analysis. Respondents in this study were village officials and aid recipients in Bedaro Rampak Village, totaling 32 people. The result of this study indicates that the transparency variable has a significant and positive effect on the BLT-DD management variable. The accountability variable also has a significant and positive effect on the BLT-DD management variable. The results of the t-count value of 12.557 and the t-table value of 3.327 indicate that transparency and accountability have an effect on the management of the BLT village fund in Bedaro Rampak Village, Tebo Centre District.